Customer Satisfaction in The Banking Industry: An Empirical Analysis of Product and Service Quality at Eka Metro Bank: STUDY OF THE IMPLEMENTATION OF BUSINESS ETHICS PRACTICES IN THE OPERATIONS OF THE DIGITAL ONLINE SHOP LINSHOP - Hersanius Kurnia Peong; Vina Lucyana; Laurensius Sandrio (JURNAL AKADEMISI VOKASI, 2025)
The rapid advancement of digital technology has significantly transformed business operations, particularly among Micro, Small, and Medium Enterprises (UMKM) in Indonesia. One of the essential aspects determining the success of digital businesses is the implementation of business ethics as a foundation for building consumer trust. This study aims to analyze the application of business ethics in Linshop’s digital operations, specifically in promotional activities, transactions, and customer service, as well as to identify the challenges faced in maintaining ethical principles amid competition and shifting consumer expectations. This research employs a qualitative descriptive method through field observations and in-depth interviews with the owner, employees, and loyal customers. The findings reveal that Linshop applies business ethics through honest product information, price transparency, responsive customer service, and willingness to acknowledge mistakes when they occur. These ethical practices significantly contribute to shaping consumer trust, reflected in customer loyalty and repeated purchases. The results align with previous literature, emphasizing that business ethics in digital contexts serves not only as a moral guideline but also as a strategic factor for strengthening business reputation and credibility. However, Linshop also faces several challenges, including price pressure, expectations for rapid responses, and platform limitations that affect information transparency. Overall, this study confirms that business ethics play a crucial role not only as moral conduct but also as a competitive strategy for sustaining digital-based UMKM.